2020
DOI: 10.1016/j.ijscr.2020.09.193
|View full text |Cite
|
Sign up to set email alerts
|

Huge gangrenous gallbladder presenting as gastro-esophageal reflux disease successfully treated by laparoscopic cholecystectomy: Case report and literature review

Abstract: Highlights “Giant” gallbladder development in the context of acute on chronic cholecystitis is extremely rare and may present with atypical symptoms secondary to mass effect. Current grading systems for acute cholecystitis severity do not include assessment based on size making them insufficient in predicting “giant” gallbladder surgical prognosis. Laparoscopic cholecystectomy was performed successfully despite the large gallbladder size without intraopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Figure 7 clearly indicates the importance of bilirubin as an indicator of malignant biliary obstruction, where the cut-off value for bilirubin concentration serves as an indicator for the type of disease (i.e., above 11 µmol/L choledocholithiasis is likely, and above 59 µmol/L a neoplasm may be suspected). This is in line with the previous model of the less complete closure caused by the cholestasis [ 79 ]. The ratio of conjugated to unconjugated BSs was found to be a significant indicator for healthy patients (thus the line is below the diagonal [ 80 ]) when compared with cholestasis and neoplasm patients, with a ratio of 80.3 and 48.7, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Figure 7 clearly indicates the importance of bilirubin as an indicator of malignant biliary obstruction, where the cut-off value for bilirubin concentration serves as an indicator for the type of disease (i.e., above 11 µmol/L choledocholithiasis is likely, and above 59 µmol/L a neoplasm may be suspected). This is in line with the previous model of the less complete closure caused by the cholestasis [ 79 ]. The ratio of conjugated to unconjugated BSs was found to be a significant indicator for healthy patients (thus the line is below the diagonal [ 80 ]) when compared with cholestasis and neoplasm patients, with a ratio of 80.3 and 48.7, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Various studies have shown that direct operating theatre costs are calculated and range from £14 to £40 per minute in the NHS and $30 to $100 per minute in the USA. Surgical care accounts for approximately one-third of healthcare costs and aggregates half of the inpatient hospital costs 8, 25,26,27,28,29 . One of the factors for poor theatre utilization was over-or underbooking theatre lists and unexpected cancellations costing the different healthcare systems millions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Tokyo Guidelines 9 predominantly consider preoperative factors, while the AAST 12 and PGS 11 guidelines focus on intraoperative factors assessed preoperatively through imaging. Elkbuli et al 29 underscore the drawbacks of existing tools, emphasizing the misalignment of preoperative ndings with intraoperative exploration. The authors highlighted that the PGS is promising for capturing gallbladder appearances but failed to detect its de ciency in considering gallbladder size, a crucial factor related to complications.…”
Section: Discussionmentioning
confidence: 99%
“…Giant gallbladders are associated with various obstructions of the cystic duct of the bile duct, such as stones, parasites, or tumors. [1,7,8] There are also sporadic reports of gallbladder neck gangliocytopenia leading to dilated gallbladder. [6] In this patient, there was no cystic duct obstruction or any other underlying disease.…”
Section: Discussionmentioning
confidence: 99%